TABURAR: UNDERSTANDING MODERATION THROUGH HOUSE DOORS IN THE UGAR VILLAGE - Putri Ayu, Kurnia; Yamin, Ade; Sahib, Rahmawansyah; Prasojo, Zaenuddin Hudi (Harmoni, 2023)
This study aims to reveal the moderation practices carried out by the people of Ugar village, Kokas district, Fakfak Regency, West Papua Province, through their house doors (Taburar). It departs from the assumption that there are functions and roles on the house door as a picture of mutual trust in which the community holds fast to the village philosophy as a basis for values and norms used to regulate family and community life. This traditional philosophy has enabled the Ugar community to survive and adapt to new understandings that enter their village. Qualitative research method with observation and interview techniques related to cultural phenomena and community activities. Several references were used to enrich the data. This paper found that every house in the Ugar community has many doors with their respective characters. Each character has a philosophy and value that leads to the formation of moderation. The internalization of this traditional value allows the strengthening of religious moderation and respect for other identities to occur.